Strengthening Of Employee Performance Through Work Ethic And Leadership Style - Garry Rudiarto Sukarno Putra; Tjiptogoro Dinarjo Soehari (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study aims to analyze how the influence of work ethic, work discipline and leadership style on the performance of the employees of the Production Department of PT. Adil Makmur Fajar. The population of this research is production employees of PT. Adil Makmur Fajar with a total sample of 39 people. Methods of data analysis using SPSS 25. Work ethic has a significant effect on the performance of employees in the Production Department of PT. Adil Makmur Fajar. Work discipline cannot be analyzed further because it does not pass the heteroscedasticity test. Leadership style has a positive and significant effect on the performance of employees in the Production Department of PT. Adil Makmur Fajar. Work ethic and leadership style together have a positive and significant effect on the performance of the employees of the Production Department of PT. Adil Makmur Fajar. The contribution of this research is to become input for PT Adil Makmur Fajar to determine policies and focus more on maintaining and improving the work ethic, work discipline and leadership style of the Production Department employees.